Assessing the Impact of the Maternity Capital Policy in Russia Using a Dynamic Model of Fertility and Employment - Fabian Slonimczyk; Anna Yurko (Institute for the Study of Labor (IZA), 2013)
With declining population and fertility rates below replacement levels, Russia is currently facing a demographic crisis. Starting in 2007, the federal government has pursued an ambitious pro-natalist policy. Women who give birth to at least two children are entitled to maternity capital assistance (11,000). In this paper we estimate a structural dynamic programming model of fertility and labor force participation in order to evaluate the effectiveness of the policy. We find that the program increased long-run fertility by about 0.15 children per woman.
Keywords: J13; C61; 330; fertility; female labor supply; structural estimation; Russia